Extremely - low cycle fatigue fracture of Q235 steel at different stress triaxialities. (June 2020) - Li, Zeshen; Xu, Jinjun; Demartino, Cristoforo; Zhang, Keshi
Abstract: This study presents an experimental and numerical investigation on the Extremely-Low Cycle Fatigue (ELCF) behavior of Q235 structural steel under different stress states and large strain amplitudes. A set of Q235 structural steel cylindrical specimens of different radii of curvature were selected to examine the effect of the triaxial state of stress on the fracture behavior. Cyclic axial tension-compression loading tests characterized by large strain amplitudes were conducted to obtain the hysteresis loops and the failure process by measuring both macroscopic and microscopic fracture morphologies. The results shows that, the failure behavior of Q235 steel in ELCF loading is a mixture of fatigue fracture and ductile fracture. Specimens with different stress triaxialities are characterized by different failure modes. A fracture criterion, namely the Combinatory Work Density Model (CWDM), was calibrated based on the test results. Furthermore, a cyclic plasticity constitutive model, i.e., the Chaboche model, was calibrated to describe the yield and cyclic hardening behaviors of the Q235 structural steel. Finite element (FE) simulations in the commercial software ABAQUS accounting the calibrated CWDM and Chaboche model were carried out to evaluate the fracture characteristics with different stress triaxialities and their stress-strain hysteretic curves under ELCF loading. The simulation results demonstrate that the developed FE model can reproduce the hysteretic characteristics and capture the failure process of Q235 structural steel. The proposed practical numerical tool can be used for the ELCF failure prediction in steel structures under complex stress state. Highlights: Extremely- low cycle fatigue (ELCF) loading tests were conducted on Q235 steel. Effects of different stress states and large strain amplitudes were investigated. Microscopic and macroscopic morphological were examined. ABAQUS subroutine VUMT was developed accounting the calibrated models.